Policies to Develop Transportation Systems - Nasma Maan mohammad; Assda Abdulhamed Altuhafi; Basma Abdulnafi saaied (Iraqi Journal of Architecture and Planning, 2018)
Al-Alawi region is the most important transportation center of Al- Karkh district in the city of Baghdad, its importance to this district the same as the beating heart for the human body, where it has a number of privileges including association of all axes destinations movement that lead to important government institutions, such as building of the Iraqi Museum, the train station, government buildings and others. Many inside transportation vehicles move out and back to this center as well the external transportation vehicles do, either to the northern, southern, eastern and western sides of Iraq, or to the outskirts of the city of Baghdad. It is also surrounded by housing complexes vitality and tourism companies that deal with many kinds of travelers inside or outside Iraq, in addition of all that, it plays a great role in facilitating the movement of population to Rusafa, beside of its heritage and historical importance. Unfortunately, this region is currently experiencing high traffic jams and cross circulation between the movement of people and vehicles. From this point, we come to the definition of the research aim, which is that the importance developing policies and strategies to solve the problem of traffic congestion, and the intersection of movement between people and vehicles, and between vehicles themselves. To achieve the goal of this research we adopted several strategies that came in four axes, the first one discussed the problems of the study area, while the second one shows its analysis, secondly, then differentiation the theoretical framework, thirdly, at last concluding the applying operations are submitted which represented by electing four main items of detailed theoretical field, studies the process of questionnaire to the pioneers of that region, to reached the final results and come out with the conclusions that stresses on the need for separation between movement of people and vehicles and to develop the possible solutions such as placing the bridges and tunnels for pedestrians and vehicles, and electric trains, , and open additional streets, and activating the role of traffic signals, as well as the study of economic and social dimensions and services.Keywords: Baghdad City, Al- Alawi Region, Movement of People, Movement of Vehicles, Transportation System.Â